Value, utility and autonomy : a moral-critical analysis of utilitarian positions on the value of prenatal life - De Roubaix, J. A. M. (John Addey Malcolm) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2005.